La responsabilité du banquier en cas de faillite de l'entreprise financée - Gavalda, Christian (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1981)
This article by a leading specialist on Banking Law discusses the legal implications resulting from the extension or withdrawal of a line of credit by a banking institution to a failing client. French Courts consider the bank professionaly liable to it's debtor and it's debtor's creditors when credit is withdrawn without proper justification. The bank may also be liable to it's client's creditors if credit is maintained and so leaves the client's creditors under the impression that their debtor is still a going concern or hides its imminent bankruptcy. This article is of special interest to the Canadian lawyer as the french decisions are based on section 1382 of the french Code Civil similar to section 1053 C.C.